HUBUNGAN PEMAKAIAN ALAT KONTRASEPSI SUNTIK DENGAN PERUBAHAN SIKLUS MENSTRUASI PADA AKSEPTOR KB DI KLINIK NURJAIMAH KECAMATAN GEBANG KABUPATEN LANGKAT TAHUN 2016 - Aisyah Aisyah (Universitas Prima Indonesia, 2018)
Family Planning Program (KB) one of the basic social programs. That is very important for the progress of the nation. This program contributes greatly to the development of human resources in the present and the future, which is a prerequisite for the progress and independence of the nation. Family Planning Program means to achieve a just, prosperous and prosperous society (BKKBN, 2011). The purpose of this study is to determine whether there is a relationship between the use of contraceptive injections with the menstruation cycle on the family planning acceptor at Nurjaimah Clinic Gebang District in 2016. This type of research is a quantitative description research using correlation research method with the number of samples of 40 peoples. The results of the study revealed that based on the intravenous contraception of 40 respondents, the majority used the 3-month injection (Progesterone) as much as 62.5% and the minority used the 1 month injection (Progesterone and Estrogen) as much as 37.5% that based on the change of menstrual cycle from 40 respondents majority there is change as much (52,5%) and minority there is no change as much as (47,5%) The conclusion of this research is there is relation between usage of injection contraception tool with change of menstrual cycle at acceptor KB where at a significant level (α) = 5% (0,05) the result p.value = 4,177 at df = 1 where X2count> X2table (4,117> 3,841) or sig <α (0,041 <0,05) guidance counseling is given periodically to acceptors to improve the stability of acceptors in the use of contraceptives and recommended not to move the contraceptive and to improve the quality of counseling given primarily related to modesty, simplicity of language and affirmation of all material counseling, because these three things have the strongest impact on the understanding so that it also affects the stability of acceptors.